Inklusi Keuangan Syariah dan Pemberdayaan UMKM Berkelanjutan (Studi pada KSPPS BMT Artha Buana Metro) - Muslimin, Ahmad; Ashari, Fuad; Kusno Aji, Didik (Bulletin of Community Engagement, 2021)
This research aims to determine the Sharia financial inclusion program at KSPPS BMT Artha Buana Metro to increase the empowerment of MSMEs. The research method used in this research is qualitative with a phenomenological approach. This research indicates that KSPPS BMT Artha Buana Metro has implemented Sharia financial inclusion well. This research also shows that social capital is vital in implementing financial inclusion. Good social capital is defined by several indicators: ease of access, ability to use, suitability to needs, training and supervision. KSPPS BMT Artha Buana Metro has provided many products and facilities so that MSMEs can obtain capital and use it to develop their business and improve the overall sustainable economy. In summary, the findings of this research accentuate the importance of well-implemented Sharia financial inclusion programs, driven by robust social capital, in promoting the empowerment of MSMEs and fostering a resilient and sustainable economy. Keywords: Sharia Financial Inclusion, Empowerment MSMEs, Financial Inclusion Program